Proclaiming the gospel in Macedonia, Achaia and in every place. Missions and 1 Thessalonians 1:6-8 - P. G. R. de Villiers (Acta Theologica)
In this article the author analyses 1 Thessalonians 1:6-8 in order to illuminate missiological activities of Pauline Christianity. Paul is often regarded as the zealous missionary who took the rural, Palestinian gospel of Jesus to key cities in the Roman Empire and thus contributed decisively to the founding of Christianity. Information in this passage gives a more balanced picture of Pauline mission, illuminating its corporate nature, its outward nature and its expectations that converts should become actively involved in spreading the word in a life-embracing manner.